HUBUNGAN GAYA KEPEMIMPINAN DEKAN DENGAN SEMANGAT KERJA DOSEN DAN KARYAWAN FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG - Muhammad Said (JURNAL KOMPETITIF, 2013)
This study aims to determine to find out how much the relationship between Dean leadership style with employee morale and lecturer at the Faculty Economics, University of Tridinanti Palembang. In this study used probability sampling with a sample of 25 people.. From the results of statistical analysis known to a significant degree of leadership style variables (X) of 0.003 (p ≤ 0.05), indicating that leadership styles have a significant effect on morale. Correlation coefficient between the variables of Leadership Styles (X) with a variable work spirit (Y) of 0.570 or 57%, this suggests there is quite a strong correlation between two variables. Thus the organization's goals will be reached in case of cooperation between leaders and subordinates, because the success or failure of a leader will be influenced by his subordinates, and leader ability to build the morale of subordinates is required. Key word: Leadership Style and Employee Morale